Handbook of industrial mixing : science and practice - Paul, Edward L., ....- (Hoboken : Wiley, 2004)
Samenvatting:Handbook of Industrial Mixing will explain the difference and uses of avariety of mixers including gear mixers, top entry mixers, side entrymixers, bottom entry mixers, on-line mixers, and submerged mixers TheHandbook discusses the trade-offs among various mixers, concentrating onwhich might be considered for a particular process. Handbook ofIndustrial Mixing explains industrial mixers in a clear concise manner,and also:* Contains a CD-ROM with video clips showing different type of mixers inaction and a overview of their uses.* Gives practical insights by the top professional in the field.* Details applications in key industries.* Provides the professional with information he did receive in school
CDrom included
Keywords: Productietechnologie : Mengen; Vloeistoffen